Thermal and Gluing Properties of Phenol-Based Resin with Lignin for Potential Application in Structural Composites - Galdino, Danilo Soares [UNESP]; Kondo, Marcel Yuzo [UNESP]; De Araujo, Victor Almeida [UNESP]; Ferrufino, Gretta Larisa Aurora Arce [UNESP]; Faustino, Emerson; Santos, Herisson Ferreira dos; Christoforo, André Luis; Luna, Carlos Manuel Romero [UNESP]; Campos, Cristiane Inácio de [UNESP] (MDPI, 2023)
Using Kraft lignin, bio-based adhesives have been increasingly studied to replace those petrochemical-based solutions, due to low cost, easy availability and the potential for biodegradability of this biomaterial. In this study, lignin-based phenol-formaldehyde (LPF) resins were synthesized using commercial Eucalypt Kraft Lignin (EKL), purified at 95%, as a phenol substitute in different proportions of 10%, 20%, 30% and 50%. The properties of bio-based phenol formaldehyde (BPF) synthesized resin were compared with phenol-formaldehyde resin (PF) used for control sampling. The results indicated that viscosity, gel time and solid contents increased with the addition of pure EKL. The shear strength test of glue line was studied according to American Society for Testing and Materials (ASTM), and BPF-based results were superior to samples bonded with the PF as a control sample, being suitable for structural purposes. Changes in the curing behavior of different resins were analyzed by Differential Scanning Calorimetry (DSC), and sample comparison indicated that the curing of the LPF resin occurred at lower temperatures than the PF. The addition of EKL in PF reduced its thermal stability compared to traditional resin formulation, resulting in a lower decomposition temperature and a smaller amount of carbonaceous residues.
Keywords: bio-based resin; lignin-phenol-formaldehyde; structural composites